Compact reconfigurable PIFA antenna for wireless applications - Abdullah Ali Jabber; Ali Khalid Jassim; Raad Hamdan Thaher (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
This paper presents, new compact and multiband frequency reconfigurable planar inverted-F antenna (PIFA). The antenna is designed and optimized to cover mobile application devices like GPS, WLAN/Wi-Fi, WiMAX, 4G LTE, UWB, and satellite applications. The frequency reconfigurability is obtained by using only a single RF switch (PIN diode) for changing the operating frequency. The antenna dimensions are 45.6x39.6x1.6 mm3 printed on an FR-4 epoxy substrate with relative dielectric constant εr = 4.3, loss tangent tan (δ) = 0.002 and 50 Ω coaxial feed line. The proposed antenna has two patches connected by a single PIN diode. The antenna introduces nine resonant frequencies under (S11 ≤ -10 dB) which are: 0.980 GHz, 3.392 GHz, 3.924 GHz, 4.554 GHz, 5.82 GHz, 6.81 GHz, 7.305 GHz, 8 GHz and 8.105 GHz in the ON and OFF states of the PIN diode which are applicable to cover GSM900, WLAN/Wi-Fi, WiMAX, 4G LTE, UWB, and satellite systems. The obtained maximum simulated gain is 8.45 dB at 6.81 GHz. The lowest return loss is obtained to be -42 dB at 5.854 GHz. Detailed simulation and measurement results are explored and studied in this research. The CST software is used to simulate and optimize the proposed PIFA antenna. The proposed antenna has been fabricated and produced a good agreement with the simulation results.